Al-Yaqubi's Sources and the question of Shia partiality (Journal of the College of Education for Women, 2019)
Al-Yaqubi was biased in favor of Shia. May be du to his choice of source, materials. All historians as with other human beings are biased in their attitudes and preconceptions in one degree or another as well as in one direction or another.The choice of source materials, their nature and the use made of them is an important index for measuring the achievement of ang historian.Several specific questions arise. What sources did author use that were either unknown to or were not employed by his predecessors and contemporaries for whatever reason?What sources are common to al- Yaqubi and his colleagues among the early Arab historians and what evidence of tendentiousness can be ascert- ained in these? To what extent can the author's tend be attributed to his selection of sources materials to the way in which he manipulated these? Answers to some of these questions should help to clarify the Relationship between al-Yaqubi's work and those of his historical confreres.